Synthesis and characterization of new imidazolidineiminothione and bis-imidazolidineiminothione derivatives as potential antimicrobial agents - Ammar, Yousry Ahmed; Abbas, Samir Youssef; El-Sharief, Marwa Ahmed Mohamed Shehab; Salem, Mohamed Abd El-Rashid; Mohamed, Ahmed Ragab (European Journal of Chemistry, 2017)
A series of new imidazolidineiminothiones (2-4) and bis-imidazolidineiminothiones (5) were synthesized through the cycloaddition reaction of N-arylcyanothioformamides (1) with some electrophilic reagents. Structure of imidazolidineiminothione derivatives were established based on spectroscopic IR, 1H NMR, 13C NMR, MS and elemental analyses data. These compounds were screened for their antibacterial and antifungal activities. Among the synthesized compounds, imidazolidineiminothione derivative 3a showed about 25% less potent effect than Ampicillin against S. epidermidis and B. subtilis (MIC, 0.49 μg/mL) and about 50 % less potent effect than Amphotericin B against A. clavatus and G. Candidum. Bis-imidazolidineiminothione derivative 5a was equipotent to the Gentamycin in inhibiting the growth of N. gonorrhoeae (MIC, 0.49 μg/mL), and displayed 50% less active than Amphotericin B against A. clavatus.